2005
DOI: 10.1080/10473289.2005.10464699
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carbonaceous Species of Ambient PM2.5 in Beijing, China

Abstract: One-week integrated fine particulate matter (i.e., particles Ͻ2.5 m in diameter; PM 2.5 ) samples were collected continuously with a low-flow rate sampler at a downtown site and 18%, respectively, higher than those at Chegongzhuang, which could be attributed to different local emissions of primary carbonaceous particles and gaseous precursors of SOC, as well as different summer photochemical intensities between the two locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
(45 reference statements)
0
11
2
Order By: Relevance
“…The SOC / OC was higher than 0.5 during almost the whole sampling period, except on 30 January when the third haze event occurred. This ratio was higher than most of the results found in other areas such as in Beijing and Guangzhou (Yang et al, 2005;Tan et al, 2009). …”
Section: General Characteristics Of Haze Eventscontrasting
confidence: 73%
See 2 more Smart Citations
“…The SOC / OC was higher than 0.5 during almost the whole sampling period, except on 30 January when the third haze event occurred. This ratio was higher than most of the results found in other areas such as in Beijing and Guangzhou (Yang et al, 2005;Tan et al, 2009). …”
Section: General Characteristics Of Haze Eventscontrasting
confidence: 73%
“…The relatively high ratios of OC / EC (10.6 ± 4.29), which were higher than the ratios in Beijing (7.1 ± 0.5) and Jinan (7.15 ± 1.78), demonstrated the existence of secondary organic carbon (SOC) Zhang et al, 2014). The concentrations of SOC were estimated by applying the EC tracer method, which has been widely used to estimate the secondary organic aerosol contribution to PM 2.5 concentrations (Castro et al, 1999;Yang et al, 2005). The minimum ratio of OC / EC was 3.09 in the present study.…”
Section: General Characteristics Of Haze Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies usually determined the chemical compositions and optical properties of atmospheric aerosols separately [8][9][10]. Yang et al [11] compared the characteristics of PM2.5 in representative megacities of China.…”
Section: Introductionmentioning
confidence: 99%
“…A major interest is on the carbonaceous fraction, which makes up a major fraction in PM. Studies reported between 8% and 53% of total carbon (TC) in PM 2.5 samples in Italy [5], 26% to 39% in PM 2.5 and 20% to 27% in PM 10 in California [6] or between 21% and 28% in PM 2.5 samples in different cities in Korea and China [7][8][9]. Whereas elemental carbon (EC) is emitted by combustion processes, organic carbon (OC) can also be of biogenic origin.…”
Section: Introductionmentioning
confidence: 99%